Health Care Centralization: The Health Impacts of Obstetric Unit Closures in the US - Stefanie Fischer; Heather Royer; Corey White (Institute of Labor Economics (IZA), 2023)
Over the last few decades, health care services in the United States have become more geographically centralized. We study how the loss of hospital-based obstetric units in over 400 counties affect maternal and infant health via a difference-in-differences design. We find that closures lead mothers to experience a significant change in birth procedures such as inductions and C-sections. In contrast to concerns voiced in the public discourse, the effects on a range of maternal and infant health outcomes are negligible or slightly beneficial. While women travel farther to receive care, closures induce women to receive higher quality care.
Keywords: J13; I18; J08; J18; I38; 330; obstetric; closure; infant health; maternal health; maternity ward; hospital quality